Henry James’s “The Jolly Corner”1: Revisiting the Parable of the Prodigal Son (Luke 15:11–32) - Jack, Alison M. (Journal of the bible and its reception, 2014)
In this article, various reception-historical analyses of Henry James’s short story “The Jolly Corner” and its use of the Bible are subjected to critique. The parable of the Prodigal Son is offered as a convincing and significant intertext which is clearly signalled in the story. Reading this parable in the narrative yields useful insights into the dynamics between the characters, and suggests a psychological rather than supernatural interpretation of events.